Insights regarding the applicability of semiotics to CSR communication research - Yekini, Kemi C. (Edward Elgar, 2017)
The chapter argues for a linguistic based theory and analytical tool – Semiotics in evaluating the quality and authenticity of Corporate Social Responsibility Reports (CSRR). Despite the proliferation of studies on CSR communication, there is lack of consensus and cardinal methodological base for evaluating the quality of CSRR. Over the decades, the findings from the enormous studies on the subject have remained conflicting, unintegrated and often pedestrian or overlapping. Drawing on Semiotics – a linguistic-based theoretical and analytical tool, this chapter explores an alternative perspective to evaluating the quality and veracity of CSR reports. The author proposed a two-phased model that employed the Greimas semiotics narrative schema and the semiotic square of veridiction in drawing meanings from CSRR. The chapter advances CSR communication research by introducing a fundamental theoretical methodology.